Enhancing the Role of the Audit Board of the Republic of Indonesia in Fraud Detection - Indra, Indra; Iskak, Jamaludin; Khaq, Akhsanul (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2022)
This study aims to investigate the rise of rampant fraudulent behavior committed by officials of government entities and explore the development of fraud detection performed by the Audit Board of Indonesia (BPK RI) in Indonesia. This study has three objectives. First, it investigates how officials of government entities in Indonesia committed fraud. Second, it aims to discover the role and performance of BPK in preventing fraud. Third, it aims to recognize the development of audit findings as a result of identified fraud and the contribution made by BPK in detecting fraud in government entities. This study was based on the analysis of study literature and other secondary data sources. This study has identified that the primary role and responsibility of BPK is to detect fraud that will cause material adverse impacts on the government's financial statements. Ergo, disregarding fraud will undermine BPK's reputation and lead to distrust in the quality of external audit findings. Based on the study results, the author suggests that auditors should further sharpen the audit process by providing sufficient evidence and executing audit standards accordingly during the audit process to provide better opinions and recommendations for fraud eradication. In addition, the insights drawn from this study can be used to develop other research instruments (e.g., questionnaires or interviews) to disclose empirical evidence on fraud detection in government entities throughout Indonesia.